Endoscopic Features of Chronic Liver Disease Patients Admitted in a Tertiary Care Hospital in Bangladesh- A Cross Sectional Study - Siddiqua, Ayesha; Rishad, Mahbub Mayukh; Noor, Nawsabah; Reza, Ishrat Binte; Das, Aparna; Ahasan, H A M Nazmul (Journal of Medicine, 2023)
Background: Chronic liver disease is a major burden with increased rates of morbidity & mortality worldwide. The role of endoscopy in liver disease is both diagnostic and interventional and a key to achieving a better outcome for the disease. Multiple presentations of CLD can be found at endoscopic evaluation. This study aimed at evaluation of the pattern of presentation of the endoscopic features of the admitted patients in Dhaka Medical College Hospital. Materials & Methods: This cross-sectional study was conducted over 100 adult patients of Chronic Liver Disease in Dhaka Medical College Hospital, from 1st of July 2019 to 31st of December 2019. After getting written informed consent, a detailed history, clinical examination, relevant investigations and upper GI endoscopy was carried out in each patient. All the methods in the present study were carried out following the ethical guidelines of the 1975 Declaration of Helsinki. Data were recorded in separated case record form and analyzed by IBM SPSS version 26. Results: Our study found that majority (43%) of the patients were aged between 41 to 50 years; 69% were male & 31% female. Mostly Hepatitis B virus infection was the etiology. The commonest (38%) endoscopic finding being the presence of both esophageal & gastric varices along with Grade III varices encompassing the largest entity (63.4%). Conclusion: More than half of the patients with gastro-esophageal varies has Grade III varices putting them in higher risk of morbidity and mortality. J MEDICINE 2023; 24(2): 135-138